Performance analysis of CHECKSUM and HASH function in database / Nurhanim Izyani Halim - Halim, Nurhanim Izyani (2019)
As the data are grow day by day in the database, the performance of the database will be effected. Other than that, the additional features or setting for example the security technique which is to ensure the integrity of the database that are apply on the database also will be effected the performance of the database. To counter this problem, the author design a hybrid technique which is combination of CHECKSUM and SHA2_512 in order to secure the database from being attack. This technique will be applied in the database and the performance metric of time will be evaluated and compare with the current technique such as CHECKSUM, MD5 and SHA2_512. In order to complete this study, the author write the hybrid technique by using language of SQL and apply in the SQL database. The performance metric of time that want to evaluate is based on the CPU time and elapse time when to accessing the data in the database. Through the testing, the result shows the proposed technique which is hybrid technique can be applied in the database.